Research on Hydrophobic Properties of Grating Structure on Monocrystalline Silicon Fabricated Using Micromachining - Wenyu Ding; Ziyang Cao; Bangfu Wang; Shunjie Xu; Zhongwang Wang (Advances in Materials Science and Engineering)
In this paper, micromilling was used to process the surface of single crystal silicon, and six different structural parameters of the grating structure were tested to get the contact angle in a different wettability. The contact angle obtained by the experiment was compared with the theoretical values of the Wenzel and Cassie model optimized based on the characteristics of micromilling. The relationship between structural parameters and wettability was verified. First, the contact angle of the parallel grating structure was greater than the vertical direction, which was influenced by the solid-liquid interface tension. Second, the hydrophobicity of the specimen was in good agreement with the predicted trend of the optimized prediction model C when the width of the convex is reduced. The support of the theoretical model to the experimental results is instructive to the construction of the structure. In addition, the molecular dynamics were used to verify the hydrophobicity of grating structures from a molecular point of view.